Prevalence Of Hypertension Amongst Workers of a Fertilizer Company in Surat District - Vidita Divan; Vineeta Chauhan; Shaishav Panchal; RK Bansal (Medsci Publications, 2010)
This cross sectional study explores the prevalence of hypertension, whether diagnosed or undiagnosed, amongst 104 employees of a fertilizer company in Surat district along with its association between different variables such as age, education, tobacco use, alcohol use by chi-square test and fisher exact test.